2019
DOI: 10.18510/hssr.2019.75165
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Malaysian International High School Students’ Performance: The Moderating Effect of Transformational Leadership

Abstract: Purpose of the study: This study intends to scrutinize the factors affecting Malaysian international high school students’ academic performance. Methodology: 117 responses were collected randomly using a questionnaire. The data were analyzed using Partial Least Square (PLS) Main Findings: The findings revealed that future goals as the most crucial factor besides peers’ support, teachers’ support and self-efficacy. Furthermore, it was also disclosed that TL moderated only the self-efficacy on Academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Leadership is a process of influencing a group of individuals to achieve a common goal or vision [11]. On top of that, educational transformational leadership is an important aspect that shapes the culture and effectiveness of a school.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Leadership is a process of influencing a group of individuals to achieve a common goal or vision [11]. On top of that, educational transformational leadership is an important aspect that shapes the culture and effectiveness of a school.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Leadership is a process of influencing a group of individuals towards a common goal or vision performance (Alnawasreh, Nor & Suliman, 2019). On top of that, transformational leadership is an important aspect of shaping the culture and effectiveness of a school, and it was found that effective transformational leadership could positively influence job satisfaction and teacher commitment (Wahab, Faud, Ismail & Majid, 2014).…”
Section: Introductionmentioning
confidence: 99%